Digital Governance and Corporate Raids: Factors of Interdependence, Ways of Counteraction - Oleksiy TITARENKO; Anna POLITOVA; Mykhailo AKIMOV; Andrii PRYKHODKO; Roman YEMELIANOV; Jaroslaw SZREDER (Communications of International Proceedings, 2021)
Corporate raiding is a pervasive problem and severely threat to economic and social development . The phenomenon of raiding often examined from the country’s broader problem of endemic corruption. Paper scrutinizes a hypothesis that implementing of digital technologies to transform public administration organizations and their relationships with business, NGO, citizens and each other don’t necessary help reduce the level of corporate raiding without severe sanctions and enhance Ukrainian officials who assist raiders  use sophisticated schemes of corruption. This research sheds light on the causes and factors of interdependence between digital tools and attacks on corporate property as well as ways of counteraction of raiding in Ukraine using digital tools.
Keywords: corporate raids; corruption; corruption offences; reasons; counteraction; economical security.